Structure and spatial patterns of trees in old-growth northern hardwood and mixed forests of northern Maine - Chokkalingam, U.; White, A. (2001)
Stand structure including spatial patterns was studied in northern hardwood and mixed forest types in the 2000-ha old-growth Big Reed Forest Reserve in northern Maine using complete stem mapping, dendrochronology, and spatial analyses on ~0.5 plots. The inclusion of saplings, dead wood, age distributions, spatial pattern, and interactions provided some idea of underlying processes and temporal change. Structural characteristics were most comparable to spruce-northern hardwood forests of northern New England and New York, and most characteristics matched expected patterns for old-growth forests of the region.Results indicated smaller maximum-tree sizes, lower basal areas (26–34 ) and downed-wood volumes (29–64 ), higher densities (475–649 ), but similar species longevities compared to other mesic old-growth forests further south and in the Lake States. The stands were dominated by very shade-tolerant tree species, including Fagus grandifolia Ehrh., Acer saccharum Marsh., Picea rubens Sarg. and Abies balsamea (L.) Mill, with each species found in many crown positions and age and size classes. The sapling layer was dominated by Fagus grandifolia followed by Picea rubens. Most species had reverse-J shaped diameter distributions, but age distributions were indicative of synchronous, episodic recruitment. In most plots, Acer saccharum diameter distributions were skewed towards the mid-larger size classes. Lack of young and small Acer saccharum stems suggested change in forest composition towards Fagus grandifolia dominance. Most species formed small-scale clusters (£15 ) perhaps in response to small gap disturbances. Snags were the dominant dead wood type and were randomly to regularly distributed in most plots. Logfall directions were unrelated to hurricane paths. Recent small-scale disturbance events and topographic position appear to be important in explaining current structure and dynamics of the hardwood and mixed forests of Big Reed Forest Reserve in northern Maine. The continued effects of beech bark disease had a greater effect on hardwood plots, whereas a recent spruce budworm outbreak had a greater effect on plots with higher conifer density.The dominance of very shade tolerant tree species in small-scale clusters, and randomly distributed snags rather than clustered uproots were indicative of the prevalence of small scale gap disturbance regimes in the hardwood and mixed forests of Big Reed Forest Reserve in northern Maine. Varying topographic position may allow for slight changes in disturbance regime leading to consequent variation in structure and dynamics. H1, a more open plot on upper exposed slopes, had distinctly different characteristics such as lower live and dead tree and sapling densities than the other plots, but more uprooted trees and Acer saccharum saplings. Such small scale gap disturbance regimes operating on an episodic basis, and effects of slight variations in this regime on stand composition and structure have significant implications for silvicultural interventions and management of these forest types.